Genome-wide identification and expression analysis of CCoAOMT genes in Capsicum annuum L. under drought stress - Wu, Di; Lu, Chen; Bai, Liwei; Yan, Xi; Lai, Wei; Zhang, Xiaoming; He, Lei; He, Jianwen (Frontiers in Plant Science, 2025)
IntroductionLignin biosynthesis is critical for plant structural integrity and stress response, with Caffeoyl-CoA O-methyltransferase (CCoAOMT) playing a pivotal role. This study investigates the CaCCoAOMT gene family in pepper (Capsicum annuum) based on the Zunla-1 genome to elucidate their molecular characteristics and drought stress responses.MethodsEleven CaCCoAOMT genes (CaCCoAOMT1–CaCCoAOMT11) were identified and analyzed for physicochemical properties, phylogenetic relationships, gene structure, conserved motifs, and promoter elements. Gene expression patterns were validated using qRT-PCR under drought stress, and subcellular localization of CaCCoAOMT1 and CaCCoAOMT2 was determined in tobacco leaves.ResultsThe CaCCoAOMT genes are distributed across chromosomes 1, 2, 4, and 8, with CaCCoAOMT10 and CaCCoAOMT11 unanchored. The encoded proteins range from 143 to 380 amino acids with 2–10 exons. Phylogenetic analysis classified the genes into clades II, III, V, and VII. Ten conserved motifs were identified, with motifs 1 and 2 present in all genes. Promoter analysis revealed cis-elements responsive to light, hormones, and drought stress. Expression analysis showed tissue- and developmental stage-specific patterns, with all genes except CaCCoAOMT6 exhibiting differential expression. Under drought stress, six genes were significantly downregulated and two were upregulated in roots. CaCCoAOMT1 and CaCCoAOMT2 localized to both the cytoplasm and nucleus.DiscussionThese findings highlight the structural and functional diversity of the CaCCoAOMT gene family and their regulatory roles in drought stress response in pepper. The differential expression and subcellular localization suggest specific roles in lignin biosynthesis and stress adaptation, providing a foundation for further functional studies and potential applications in improving drought tolerance in pepper.